2019
DOI: 10.1016/j.chempr.2019.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Thermodynamics, and Kinetics of Plinabulin Binding to Two Tubulin Isotypes

Abstract: Plinabulin is a novel tubulin-binding agent that is currently in phase 3 clinical trials for cancer treatment and prevention of chemotherapy-induced neutropenia. Plinabulin binds within a distinct tubulin pocket, which differentiates it from other tubulin binders. Aimed at disclosing structural and energetic details of plinabulin binding to tubulin, we combine X-ray crystallography and computational modeling. We compare the plinabulin residence time with that of colchicine and combretastatin-A4. Our study help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 67 publications
(71 reference statements)
3
45
0
Order By: Relevance
“…The intermediate domain movement could be characterized as a rotation of its b sheet and a translation of the H7 helix. Essentially the same conclusion can be derived from the comparison of the higher resolution data that are now available, reaching 3.1 Å in the case of the microtubule (pdb id 6DPU; Zhang et al, 2018) and 1.52 Å in that of a tubulin-DARPin complex (pdb id 6S8K; La Sala et al, 2019). Interestingly, although the H7 helix is part of the intermediate domain, the adjacent H6 and H8 helices hardly belong to any of the two domains.…”
Section: The Tubulin Conformational Changes Associated With Microtubule Assemblysupporting
confidence: 64%
“…The intermediate domain movement could be characterized as a rotation of its b sheet and a translation of the H7 helix. Essentially the same conclusion can be derived from the comparison of the higher resolution data that are now available, reaching 3.1 Å in the case of the microtubule (pdb id 6DPU; Zhang et al, 2018) and 1.52 Å in that of a tubulin-DARPin complex (pdb id 6S8K; La Sala et al, 2019). Interestingly, although the H7 helix is part of the intermediate domain, the adjacent H6 and H8 helices hardly belong to any of the two domains.…”
Section: The Tubulin Conformational Changes Associated With Microtubule Assemblysupporting
confidence: 64%
“…Support for this mechanism can be found in the structures of eukaryotic tubulins. A water molecule is found bound to a-tubulin Glu254 in the sequestered a/b-tubulin dimer (21), equivalent to the hydrolytic water bound to Glu251 in OdinTubulin (compare Fig. 4B and 4C).…”
Section: Conservation With Microtubule-forming Tubulinsmentioning
confidence: 91%
“…Importantly, plinabulin significantly reduced CIN in cancer patients when administered within 1 h following treatment with another tubulintargeted therapy, docetaxel (Taxotere ® ) [9] [Mohanlal et al, ASCO-SITC 2018, Abstract 126]. This effect stands in contrast to the worsening of CIN by combretastatin A4 [14], a small molecule that also binds to the colchicine pocket, but at a site and with kinetics that differ from that of plinabulin [15]. Studies reported here aimed to determine whether plinabulin could act as a broad acting anti-CIN agent with multiple chemotherapies of diverse classes, utilizing a mechanism distinct from approved therapies that increase circulating G-CSF.…”
Section: Introductionmentioning
confidence: 99%